Desechos electrónicos: gestión de su valor oculto (2021)
ing: In Colombia, it is estimated that in 2013 about 120,000 tons of WEEE and batteries were produced (Casas, 2018). According to studies carried out between 2005 and 2009, the types of waste that are most commonly found in WEEE are household appliances and consumer appliances with 39% and televisions with 14% (Ministry of the Environment and Sustainable Development, 2015) with these data there has been evidence of an indiscriminate increase in waste and mismanagement of the same that every time turn the streets of cities into dumps of electrical and electronic waste that will have a greater impact on the environment and the Human health. This research project was proposed in order to be able to evaluate the current situation of WEEE management in the town of Ciudad Bolívar, a town that is part of the intervention area of the southern Subnet of Bogotá, starting in the neighborhoods surrounding the Doña Juana landfill also seeking to determine the participation of the main actors, habits and customs and how through environmental education to find the hidden value of electrical and electronic waste that, although they are increasing, can be an economic and solution alleviating the impacts suffered by the environment due to inadequate comprehensive management.